IMPACT OF MATERNAL DIABETES AND HYPERTENSION ON THE INCIDENCE OF HYPOGLYCEMIA IN PRETERM NEONATES ADMITTED AT A TERTIARY CARE HOSPITAL IN SOUTH PUNJAB (Journal of Medical & Health Sciences Review, 2025)
Background: Neonatal hypoglycemia is a frequent and serious complication among preterm infants, often linked to maternal medical conditions. This study investigates the impact of maternal diabetes and hypertension on the incidence of hypoglycemia in preterm neonates.Objective: To assess the association between maternal diabetes and hypertension with the incidence of hypoglycemia in preterm neonates admitted at the Paeds Ward, Nishtar Hospital, Multan.Methods: A prospective observational study was conducted from 15 February to 15 August 2025 at Nishtar Hospital, Multan.168 preterm neonates (